MOTIVASI DAN PENGELOLAAN MHRD TERHADAP PENYALURAN KUR BANK BNI CABANG PEMATANGSIANTAR - Kalvin Sinaga; Sarida Sirait; Novendra Sinaga (Politeknik Bisnis Indonesia, 2018)
The Influence Of Motivation And Management Of MHRD (Management of Human Resourses Development) to The Performance Of The Distribution Of People's Business Credit (Kredit Usaha Rakyat = KUR) In PT. Bank Negara Indonesia (Persero), Tbk (BNI) Pematangsiantar Branch. This journal : Research Program 2018. The coefficient of motivation gives a value of 0.316 which means that if the motivation is better with the assumption that other variables remain and the Coefficient of Management of Human Resource Development gives a value of 0.343 which means that if the management of MHRD is higher with the assumption that other variables remain then the performance of the Distribution of People's Business Credit in PT. Bank Negara Indonesia (Persero) Tbk , Pematangsiantar Branch will increase. The results showed that both independent variables (Motivation and Management of Human Resource Development) have a positive and significant influence, partially on the dependent variable ( The Performance of Disbursement of People’s Business Credit), Regression calculation results can be seen that the coefficient of determination (adjusted R2) obtained of 0.57. This means 57% variation of variable of performance Distribution of People's Business Credit at BNI Pematangsiantar Branch can be explained by motivation variable, management of MHRD while the rest equal to 43% explained by other variable not submitted in this research. Recommended for institution of BNI Pematangsiantar Branch. In order to improve the performance of the People's Business Credit Distribution need to increase motivation.